Maltodextrin- modified starch microparticles containing benzoic acid: Physical properties and thermal stability - Marques, Gerson Reginaldo (2022)
The microencapsulation of benzoic acid by spray drying can provide amorphous characteristics, which is necessary for its application in foods. In addition, it facilitates the use of this component in a food matrix and prolongs the shelf life of the product. Thus, wall materials with high encapsulation efficiency should be used, such as modified starch and maltodextrin and their combinations. The aim of this study was to evaluate the effect of modified starch (MS) and/or maltodextrin (M) used as encapsulating agents on the chemical and physical properties, morphological parameters, and thermal stability of spray-dried benzoic acid. Three treatments were evaluated: modified starch (MS), maltodextrin (M), and a blend containing modified starch and maltodextrin (MS/M). In general, the variables studied have a significant effect on the responses. The highest efficiency was observed for the treatment MS/M (82.65%); although it presented a lower drying process yield (50%). It was observed that the use of maltodextrin contributed to improving the wettability and solubility of the microparticles since this component is highly water-soluble. The largest microparticle diameter was 19.15 μm (MS/M), and the Span ranged from 1.94 to 2.15 for all treatments, indicating good homogeneity in relation to the particle size distribution. Concerning the particle morphology, the treatment MS/M exhibited partially rough microparticles, while the treatments MS and M led to a higher amount of brittle microparticles. The GAB model was chosen as the best model to explain the isotherm behavior. In addition, the adsorption isotherms of the samples using blend showed a Type-III behavior (non-sigmoidal), common for many foods rich in soluble components. The treatment MS/M has proven to be the most suitable for the encapsulation of benzoic acid being a good and viable option for the food industry